Solubilization of Phospholipid by Surfactin Leading to Lipid Nanodisc and Fibrous Architecture Formation - Tomohiro Imura; Satohiro Yanagisawa; Yuri Ikeda; Ryodai Moriyama; Kenichi Sakai; Hideki Sakai; Toshiaki Taira (Molecules, 2024)
Nanodiscs belong to a category of water-soluble lipid bilayer nanoparticles. In vivo nanodisc platforms are useful for studying isolated membrane proteins in their native lipid environment. Thus, the development of a practical method for nanodisc reconstruction has garnered consider-able research interest. This paper reports the self-assembly of a mixture of bio-derived cyclic peptide, surfactin (SF), and l-α-dimyristoylphosphatidylcholine (DMPC). We found that SF induced the solubilization of DMPC multilamellar vesicles to form their nanodiscs, which was confirmed by size-exclusion chromatography, dynamic light scattering, and transmission electron microscopy analyses. Owing to its amphiphilic nature, the self-assembled structure prevents the exposure of the hydrophobic lipid core to aqueous media, thus embedding ubiquinol (CoQ10) as a hydrophobic model compound within the inner region of the nanodiscs. These results highlight the feasibility of preparing nanodiscs without the need for laborious procedures, thereby showcasing their potential to serve as promising carriers for membrane proteins and various organic compounds. Additionally, the regulated self-assembly of the DMPC/SF mixture led to the formation of fibrous architectures. These results show the potential of this mixture to function as a nanoscale membrane surface for investigating molecular recognition events.